Uji Efektivitas Ekstrak Daun Sirsak (Annona Muricata) terhadap Hama Spodoptera Frugiperda pada Tanaman Jagung (Zea Mays I) - Sulaiman Ginting; S. Edy Sumantri; Fenty Maimunah Simbolon; Muhammad Syahwal Purba (Departement of Mathematics Education, 2023)
This study aims to determine the effectiveness of soursop leaf extract (Annona muricata) on the control of the armyworm Spodoptera frugiperda on corn in the laboratory. This research was conducted at the Laboratory of the Faculty of Agriculture, Islamic University of North Sumatra, Address Karya Wisata Gedung Johor, Medan Johor District, Medan City, North Sumatra. With a height of ± 25 meters above sea level with a flat topography. The study used a non- factorial randomized block design consisting of 4 treatments and 4 replications. The treatments tested were A0 = control, A1 = 0.25% extract concentration, A2 = 0.50% extract concentration, A3 = 0.75% extract concentration. The parameters observed were the percentage of caterpillar mortality (mortality) and the percentage of caterpillar attack intensity. The results showed that soursop leaf vegetable pesticide (Annona muricata) had a significant effect in controlling the armyworm pest Spodoptera frugiperda. The most dominant treatment was A3 (0.75% extract) a mortality rate of 50.00%. Compared with treatments A0 (control) a mortality rate 10,00%, A1 (extract 0.25%) a mortality rate 20,00%, and A2 (extract 0.50%) a mortality rate 30,00%. Soursop leaf extract (A.muricata) vegetable pesticide is effective in controlling armyworm (Spodoptera frugiperda) and can suppress the intensity of S. frugiperda attack on maize so that growth is not disturbed. Soursop leaf extract (A. muricata) was tested to have a significant effect on controlling armyworm (S. frugiperda) on corn (Zea mays L) in treatment A3 with a larval mortality percentage of 50.00%.